Strategi Kepemimpinan, Disiplin Kerja, dan Kompensasi terhadap Kinerja Pegawai - Rachmawati, Maysila (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
Improving employee performance is the main goal for every organization in achieving its strategic goals. Leadership strategies, work discipline, and compensation are key factors that significantly influence employee performance. This research aims to evaluate the impact of leadership strategies, work discipline, and compensation on employee performance in a modern work environment. The research method used is a quantitative approach by collecting data through questionnaires distributed to employees from various levels and departments in the organization. Data analysis was carried out using descriptive and inferential statistical techniques. The research results show that there is a positive relationship between the implementation of effective leadership strategies, a high level of work discipline, and a fair compensation system and increased employee performance. These factors together make a significant contribution to employee motivation and productivity.